Efficient Semitransparent CsPbI3 Quantum Dots Photovoltaics Using a Graphene Electrode. Issue 12 (13th August 2019) - Tavakoli, Mohammad Mahdi; Nasilowski, Michel; Zhao, Jiayuan; Bawendi, Moungi G.; Kong, Jing
Abstract: Solution‐processed perovskite quantum dots (QDs) are promising candidates for fabrication of semitransparent and tandem solar cells due to the bandgap tunability. In this work, cesium lead triiodide (CsPbI3 ) QDs are synthesized with a stable cubic phase and efficient perovskite solar cells (PSCs) are fabricated using the ligand exchange technique. Monolayer graphene is grown by chemical vapor deposition technique and a dry process to transfer graphene on top of the device is developed. Based on this approach, an efficient inverted PSC is demonstrated with a high average visible transmittance (AVT). After optimization, PSCs based on silver and graphene electrodes with power conversion efficiencies (PCEs) of 9.6% and 6.8% are achieved, respectively. Additionally, by tuning the thickness of the active layer, a PSC with PCE of 4.95% and AVT of 53% is demonstrated, indicating the potential of CsPbI3 QDs for the fabrication of semitransparent devices applicable in windows. Abstract : Combination of a cesium lead triiodide quantum dots absorber layer with graphene electrode in an inverted perovskite solar cell is a great strategy for the fabrication of a semitransparent device with power conversion efficiency of 4.95% and high average visible transmittance of 53%, which is applicable in windows.